1999
DOI: 10.1111/j.1553-2712.1999.tb01243.x
|View full text |Cite
|
Sign up to set email alerts
|

Now That We Have the Utstein Style, Are We Using It?

Abstract: Abstract. Objectives: To examine the extent to which the Utstein style has been used for out-of-hospital cardiac arrest (OOHCA) research since its publication in 1991. The style was developed in an effort to standardize OOHCA research and reporting. Methods: To locate all OOHCA research papers published between 1992 and 1997, all issues of six emergency medicine/emergency medical services (EM/ EMS) journals were examined manually, and papers from other journals were located using computerized searches. All loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…3 Although the adoption of the Utstein style has met with certain challenges, [20][21][22] its contributors recognized the value of standardized data variables. Collection of standardized variables enables meaningful comparisons and analyses within and between studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Although the adoption of the Utstein style has met with certain challenges, [20][21][22] its contributors recognized the value of standardized data variables. Collection of standardized variables enables meaningful comparisons and analyses within and between studies.…”
Section: Discussionmentioning
confidence: 99%
“…The Utstein standard for cardiac arrest and post resuscitation research includes a large number of variables, however data collection of many of these variables pose several challenges. [20][21][22] These challenges include collecting and managing the large number of data variables as well as the use of different nomenclature by different countries and health care systems. In addition, as treatment of cardiac arrest patients becomes more sophisticated, several important variables are missing, including those important in post resuscitation care.…”
Section: Discussionmentioning
confidence: 99%
“…D'ailleurs dans la majorité des registres, un système de codification des données est mis en place. La complexité des directives d'Utstein est la cause de données enregistrées souvent incomplètes, car difficiles à remplir par les équipes préhospitalières [16]. Aussi, en 2004, une version simplifiée du questionnaire d'Utstein a été proposée [17].…”
Section: Les Variables à Recueillirunclassified
“…1 Faculty members in the department of emergency medicine at the MCP Hahnemann School of Medicine, Cone and colleagues report that in five years, from 1992 through 1997, 102 articles were published that ''should have reported'' their results using the Utstein style. The authors identified these articles using handsearching of six emergency medical services (EMS) journals, plus two electronic databases.…”
mentioning
confidence: 99%